MEDULLARY THYROID CARCINOMA: PROGNOSTIC VARIABLES AND TUMOUR MARKERS AFFECTING SURVIVAL - Hassan, Aamna; Siddique, Maimoona; Riaz, Saima; Khan, Amina Iqbal; Nawaz, Muhammad Khalid; Bashir, Humayun (Journal of Ayub Medical College Abbottabad, 2019)
Background Medullary thyroid carcinoma (MTC) is a relatively rare thyroid malignancy and its clinical course varies among patients due to its familial association. A number of prognostic factors have been studied, but the significance of these factors remains controversial. We evaluated the progression free survival (PFS) and overall survival (OS) of MTC and its association with tumour marker rising velocity and serum calcitonin (Ct) doubling time (DT). Methods: Analysis of 83 (8.7%) consecutive MTC patients registered at a single centre between 1995 and 2015. The impact of tumour respectability, TNM stage, multiple endocrine neoplasia (MEN) syndrome, local recurrence, Ct DT and Ct rising velocity on PFS and OS was analysed. Median follow-up was 4.3 years (range: 1-18 years). Results: Eighty-three (8.7%) of all thyroid cancers registered at our centre were MTC. Fifty-five males, 28 females. Mean age 39 years [range: 17-72 years]. Twenty-two were unresectable and 61 resectable. Five-year and 10-year OS was 84% and 77% respectively. Of 68 with follow up greater than a year; 20 (29.4%) were cured, 15 (22.1%) had biochemical evidence of disease, three (4.4%) had stable macroscopic disease and 30 (44.1%) had recurrent/progressive disease. Sixteen (23.5%) died. On multivariate analysis, T4 tumour, male gender, nodal and distant metastases, tumour resectibility, Ct DT less than two years and tumour marker rising velocity of greater than 0.05pg/ml/month were poor prognostic factors (p-value <0.05). Age and association with MEN syndrome had no statistically significant survival impact. Radiotherapy reduced local relapse in patients with nodal disease. Total thyroidectomy with nodal clearance lessened relapses. Conclusion: Clinical stage and pathological aspects are predictors of disease progression. Persistent biochemical evidence of MTC does not affect OS, however, Ct DT < 2 years and rapid rate of tumour marker rise predict disease progression. Keywords: Medullary thyroid cancer; Calcitonin; CEA; Calcitonin doubling time; Multiple endocrine neoplasia; MEN